2022
DOI: 10.1101/2022.09.08.507171
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitotic tethering enables en masse inheritance of a shattered micronuclear chromosome

Abstract: Chromothripsis, the shattering and imperfect reassembly of one (or a few) chromosome(s)1, is an ubiquitous2 mutational process generating localized complex chromosomal rearrangements that drive genome evolution in cancer. Chromothripsis can be initiated by missegregation errors in mitosis3,4 or DNA metabolism5-7 that lead to entrapment of chromosomes within micronuclei and their subsequent fragmentation in the next interphase or upon mitotic entry6,8-10. Here, we use inducible degrons to demonstrate that chrom… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…One feature that contributes to hotspots of HPV DNA integration are common and cell‐type specific chromosomal fragile sites, which can develop DBS during replication stress which also can lead to alteration in gene expression levels 20,82–84 . Recent studies have also found that HPV integration can occur at DBS associated with chromothripsis, which as previously mentioned can generate genome‐wide chromosomal changes and have MHS at repair junctions 85–88 . Integration next to coding regions or even distant flanking regions of genes can lead to changes like amplification, rearrangement, translocation, or long‐range cis interactions.…”
Section: Mechanisms Of Microhomology‐mediated Dna Repair Machinery In...mentioning
confidence: 99%
“…One feature that contributes to hotspots of HPV DNA integration are common and cell‐type specific chromosomal fragile sites, which can develop DBS during replication stress which also can lead to alteration in gene expression levels 20,82–84 . Recent studies have also found that HPV integration can occur at DBS associated with chromothripsis, which as previously mentioned can generate genome‐wide chromosomal changes and have MHS at repair junctions 85–88 . Integration next to coding regions or even distant flanking regions of genes can lead to changes like amplification, rearrangement, translocation, or long‐range cis interactions.…”
Section: Mechanisms Of Microhomology‐mediated Dna Repair Machinery In...mentioning
confidence: 99%
“…78,115,[122][123][124][125][126][127][128][129][130][131][132][133] Chromothripsis has been associated with various tumor types and can lead to both numerical and structural CIN, altering gene expression patterns and driving changes in cellular behavior. 122,[287][288][289] Chromothripsis can contribute to tumorigenesis in multiple ways, either beneficial or deleterious. For instance, while DNA damage can be a cause of CIN as discussed in DSBs from replication stress, it is also a significant consequence of CIN, as chromothripsis could induce extensive DNA damage and destabilize tumor cell growth, leading to apoptosis.…”
Section: Cin Paradoxmentioning
confidence: 99%
“…TopBP1 is an active protein during mitosis and is critical for maintaining genome integrity (16,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). The ability of E2-K111Q to remove TopBP1 from mitotic chromatin indicated this protein may disrupt mitosis.…”
Section: Lysine Mutations In E2 Disrupt E2 Mitotic Interaction and Ab...mentioning
confidence: 99%